ORIENTASI PASAR DAN INOVASI PRODUK, SERTA PENGARUHNYA TERHADAP KEUNGGULAN BERSAING DAN KINERJA PERUSAHAAN PADA UMKM: SEBUAH AGENDA PENELITIAN - Wiwoho, Gunarso (P4M STIE Putra Bangsa, 2019)
Successful companies are those who accurately anticipate market trends and respond quickly to changing customer needs. Market orientation acts as the lifeblood of the modern marketing era. Market orientation, being one of the most important components of strategic orientation, has a broad influence on entrepreneurial oriented companies. Market orientation is important for business enterprises and new businesses because at the initial stage they allow them to learn and adapt to the environment, quickly react to opportunities and threats. Companies that get high scores on market orientation often tend to be more entrepreneurial oriented and companies that adopt market orientation have achieved superior performance. Market orientation has a positive effect on business profitability and is the culture needed to create superior customer value, which in turn is the basis for competitive advantage Market orientation is a basic strategy of marketing practice that plays an important role in improving business performance and is one of the first strategic frameworks that provide companies with sustainable competitive advantages.